2014
DOI: 10.1371/journal.pone.0108408
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Clarified Grapefruit Juice Ameliorates High-Fat Diet Induced Insulin Resistance and Weight Gain in Mice

Abstract: To determine the metabolic effects of grapefruit juice consumption we established a model in which C57Bl/6 mice drank 25–50% sweetened GFJ, clarified of larger insoluble particles by centrifugation (cGFJ), ad libitum as their sole source of liquid or isocaloric and sweetened water. cGFJ and control groups consumed similar amounts of liquids and calories. Mice fed a high-fat diet and cGFJ experienced a 18.4% decrease in weight, a 13–17% decrease in fasting blood glucose, a three-fold decrease in fasting serum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Previously, it has been reported that dietary intake of grapefruit (Citrus paradisi) (15), Citrus unshiu (16), Citrus bergamia (17), Cit- rus sunki (18), Citrus sudachi (19), and Citrus junos (20) suppressed body weight, body fat, blood TG, and T-CHO in obese mouse models. These studies showed that hesperidin, neohesperidin, nobiletin, tangeretin, and naringin have critical roles in the effects (15)(16)(17)(18)(19)(20). The peel of immature C. tumida decreased blood TG and T-CHO similarly to other citrus fruits.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, it has been reported that dietary intake of grapefruit (Citrus paradisi) (15), Citrus unshiu (16), Citrus bergamia (17), Cit- rus sunki (18), Citrus sudachi (19), and Citrus junos (20) suppressed body weight, body fat, blood TG, and T-CHO in obese mouse models. These studies showed that hesperidin, neohesperidin, nobiletin, tangeretin, and naringin have critical roles in the effects (15)(16)(17)(18)(19)(20). The peel of immature C. tumida decreased blood TG and T-CHO similarly to other citrus fruits.…”
Section: Discussionmentioning
confidence: 95%
“…It is worth noting that, even though grapefruits are ranked fifth among the most preferred fruits, their mean score is far lower than the previous four fruits. The low preferences assigned by interviewees for grapefruit strongly contrasts with the fact that it seems to be, along with oranges, the most investigated citrus fruit by scholars, thereby highlighting its positive health impacts [5,13,17,19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of these fruits also positively affects important biomarkers and contributes to a fit physical condition, such as measured in cholesterol parameters [8,9], bone health [10], intestinal microbiota [11], antioxidant status [12] and anthropometrics [13,14]. Furthermore, citrus fruits are beneficial in preventing illnesses, such as cancer [15][16][17], dementia [18], diabetes [19,20], metabolic syndrome [21], and cardiovascular, kidney and dental diseases [17,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several authors have reported that a decrease in body weight correlated with the consumption of Citrus fruit and/ or Citrus fruit-derived polyphenols (Chudnovskiy et al, 2014;Titta et al, 2010). Although the majority of correlating interventions were pre-clinical studies, a clinical investigation (Fujioka et al, 2006) conducted with 91 obese adults clearly demonstrated that consumption of grapefruit, known to be rich in a specific flavanone, naringin, is able to induce significantly higher weight loss (À1.6 kg) than placebo after 12 weeks of supplementation.…”
Section: Anthropometric Parameters and Body Compositionmentioning
confidence: 99%